Matthew, Philo, and Mercy for Animals (Matt 12,9-14) - Wilson, Walter T. (Biblica, 2015)
After comparing Matt 12,11-12 with its synoptic parallels (Mark 3,4; Luke 13,15-16; 14,5) and with texts that discuss the treatment of animals on the Sabbath (e.g., CD 11.13-14), the passage is compared with Philonic texts (Spec. 2.89; 4.218; Virt. 81, 133, 139-140, 160; cf. Plutarch, Cato 5.5; Esu carn. 996A; Iamblichus, Vit. Pythag. 30.186; Porphyry, Abst. 3.26.6) in which the Alexandrian discerns a principle informing a law that refers to the treatment of animals, and then suggests that the principle applies by analogy to the treatment of people, illuminating the principle with reference to mercy and similar concepts